Efektivitas Kinerja Pegawai Aparatur Sipil Negara di Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Mojokerto - Hambali, Hambali; Zahro, Mir’atuz (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
The effectiveness of the performance of bureaucratic employees has a function as an illustration and track record of performance achievements over a certain period. The performance of the public bureaucracy is based on five main indicators, including productivity, service quality, responsiveness, responsibility and accountability. This study aims to determine the effectiveness of the performance of the employees of the Secretariat of the DPRD Mojokerto Regency. The research method used is qualitative-exploratory research. The results showed that the Secretariat of the DPRD Mojokerto Regency has had a good performance even though operationally there are still employees who tend to delay their duties and work. Factors supporting the effectiveness of performance are indicated by the existence of motivation through rewards for outstanding employees, punishment as an act of employee discipline, and the delegation of training and training to improve employee competence. The inhibiting factor is indicated by the low competence of employees, with an indication of the low demand for employees to increase their capacity through training and training both inside and outside the Secretariat of the DPRD Mojokerto Regency.